Collaboration between Medical Professionals and Religious Leaders in Managing Acute Respiratory Tract Infections in Toddlers - Khotimah, Siti Khusnul; Purwanti, Anik Sri (STAI Syaichona Moh. Cholil Bangkalan, 2025)
This article discusses the role of religious leaders and health workers in the prevention-provision of eucalyptus oil steam therapy for toddlers with respiratory infections in Jombang Village, Jombang District, Jombang Regency. This study is a qualitative case study approach. Data sources were selected based on competencies, including 2 health workers and 2 religious leaders, through interviews, observations, and documentation. Data were analyzed through the stages of data reduction, data presentation, and concluding extended observation and confirmation. The results of the study concluded; that collaborative religious leaders were carried out by increasing their understanding of respiratory infections, and behaving in a clean and healthy lifestyle. Health workers provide eucalyptus oil steam therapy effectively to help smooth breathing, thin secretions, relieve pain in the baby's throat.